Health gains from home energy efficiency measures: The missing evidence in the UK net-zero policy debate - A.J. Kearns; M. Bhagat; D. Rae; A. McGonigle; E. Caldow; L. Marquis; C. Dove (Elsevier, 2023)
Objectives: This study examined the health gains from a programme of external wall insulation works to homes in south-west Scotland, and in particular the impact upon hospitalisations for respiratory and cardiovascular conditions. Furthermore, to consider how evidence on health outcomes could form part of the debate around actions to meet net-zero goals in the UK. Study design: This was a two-part study. Part one involved before-and-after interviews with 229 recipient households. The second part comprised an observational study of hospital admissions in 184 postcode areas. Methods: Across three years, interviews collected thermal comfort and self-reported health data(Sf-36) in the winter months prior to installation, and again in follow-up interviews the next winter. Standarised monthly data on non-elective admissions for each set of conditions were compared between the intervention postcodes and the wider health board area over a ten year period. Results: Following receipt of wall insulation, inability to achieve thermal comfort in winter reduced by two-thirds. Improvements in thermal comfort were associated with gains in physical health scores. Relative standardised admissions fell in the treatment areas, remaining lower than the district-wide standardised rate for the majority of a five year period, this effect ending during the Covid-19 pandemic. The impact on admissions was greater for respiratory conditions than for cardiovascular conditions. Conclusion: A weak policy commitment to energy efficiency could be strengthened with further evidence of the cost-savings and reduced hospital bed demand resulting from insulations works. The potential health gain may also encourage more home owners to participate.